Analysis Of Factors On Adolescent Mental Health in Cikulur District, Lebak Regency, Banten, Indonesia - Vivi Silawati; Lusi Oktaviani; Siti Syamsiah (Griya Eka Sejahtera, 2026)
Background: Adolescents generally have good physical and mental health. However, due to various disturbances, they are vulnerable to mental health issues. Mental health has become a global issue, including in Indonesia, affecting nearly 350 million people worldwide (WHO, 2023). Objective: To examine the influence of body weight, psychological resilience, emotional state, self-confidence, academic performance, and social support on adolescent mental health.Methods: This study used a descriptive approach with an ex post facto design. The sample consisted of 89 respondents. Data were collected using a questionnaire, and multiple linear regression analysis was employed. Results: Among the adolescents surveyed, 12 (13.5%) had abnormal mental health, 19 (21.3%) were classified as borderline, and 58 (65.2%) had normal mental health. Regarding body weight, 14 (15.7%) were underweight, 59 (66.3%) had normal weight, and 16 (18%) were overweight. Psychological resilience levels were low in 14 respondents (15.7%), moderate in 46 (51.7%), and high in 29 (32.6%). Emotional state analysis showed that 13 respondents (14.6%) had abnormal emotional conditions, 19 (21.3%) were borderline, and 57 (64%) were normal. Self-confidence levels were low in 12 respondents (13.5%), moderate in 72 (80.9%), and high in 5 (5.6%). In terms of academic performance, 74 (83.1%) had adequate grades, 12 (13.5%) had good grades, and 3 (3.4%) had excellent grades. Social support was low for 11 respondents (12.4%), moderate for 69 (77.5%), and high for 9 (10.1%). All variables showed statistically significant results (p-value: 0.000 < 0.05), indicating a relationship between body weight, psychological resilience, emotional state, self-confidence, and social support with adolescent mental health among middle school students in Cikulur District. Among these factors, emotional state exhibited the strongest correlation with mental health, as evidenced by a Pearson correlation value of 0.980.Conclusion: The study indicates that body weight, psychological resilience, emotional state, selfconfidence, and social support are significantly related to adolescent mental health. Recommendations: Adolescents should enhance their social interactions and engage in positive activities within their environment. Additionally, they should set clear goals for their future aspirations